BmElmo is a factor for inhibiting Autographa Californica nucleopolyhedrovirus infection in silkworm, Bombyx mori - Wang, Zhi-sheng; Yu, Wen-jing; Ding, Xin-yi; Lu, Zhan-peng; Qin, Sheng; Sun, Xia; Wang, Xue-yang; Li, Mu-wang (Frontiers in Immunology, 2025)
Autographa californica nucleopolyhedrovirus (AcMNPV) is a DNA virus with multiple host domains, and elucidating the mechanisms of its interactions with silkworms is crucial for its widespread use. Identifying key antiviral genes and analyzing their functions is an urgent task currently. Therefore, the identification and study of host genes associated with AcMNPV invasion is of great significance in solving the issue. Engulfment and cell motility (Elmo) is an identified viral infection-associated gene primarily involved in the regulation of cell motility and essential for phagocytosis and immune responses. However, its function in the silkworm response to viruses is still unclear. In this study, the sequence of BmElmo was analyzed first. It has a CED-12 functional domain that has been highly conserved among different species. Its expression peaks during the silkworm pupal stage, followed by the moth stage. Among various tissues, BmElmo expression is highest in the gonads, followed by the silk glands. BmElmo exhibits differential expression between resistant and susceptible strains. AcMNPV replication increased significantly after BmElmo knockdown in BmN cells, and decreased significantly after BmElmo overexpression. Furthermore, the expression of Janus kinase (JNK) pathway–related genes downstream of BmElmo showed altered expression that correlated positively with the expression of BmElmo. Hence, BmElmo may inhibit AcMNPV replication in the silkworm by activating the JNK pathway. The results of this study bridge the gap in understanding the role of Elmo genes in insect immunity and provides a theoretical reference for studying the interaction between insects and baculoviruses.